1971
DOI: 10.1111/j.1476-5381.1971.tb07153.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of isoprenaline, orciprenaline, salbutamol and isoetharine on the cardiovascular system of anaesthetized dogs

Abstract: Summary1. The intravenous injection of isoprenaline, orciprenaline, salbutamol and isoetharine increased heart rate in anaesthetized dogs. Log dose-response curves obtained with a series of doses of salbutamol and isoetharine were flatter than those for isoprenaline and orciprenaline. The order of activity of the drugs in increasing heart rate was isoprenaline, orciprenaline, and salbutamol = isoetharine.2. The injection into the external iliac artery of isoprenaline, orciprenaline, salbutamol and isoetharine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Although the two log-dose response curves were of different shapes, the upper parts of each were parallel and over these dose ranges isoprenaline was 30 times more active than salbutamol. In previous studies by Ekue et al (1971) in anaesthetized dogs, isoprenaline was 200 times more active than salbutamol in increasing heart rate, but in this study full dose-response curves were not examined and the drugs were administered as single intravenous doses instead of by infusion. Neither study attempted to assess the influence of reflex vagal effects produced by the drugs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the two log-dose response curves were of different shapes, the upper parts of each were parallel and over these dose ranges isoprenaline was 30 times more active than salbutamol. In previous studies by Ekue et al (1971) in anaesthetized dogs, isoprenaline was 200 times more active than salbutamol in increasing heart rate, but in this study full dose-response curves were not examined and the drugs were administered as single intravenous doses instead of by infusion. Neither study attempted to assess the influence of reflex vagal effects produced by the drugs.…”
Section: Discussionmentioning
confidence: 98%
“…Salbutamol, a drug which has a greater effect on 12-than on 01 -adrenoceptors, has been studied by Cullum, Farmer, Jack & Levy (1969) and by Ekue, Shanks & Zaidi (1971). These workers showed that in dogs, salbutamol had approximately one-eighth the potency of isoprenaline in producing increases in femoral blood flow (a 132-adrenoceptor response) but had only one-two hundredth the potency of isoprenaline in increasing heart rate (a ,B -adrenoceptor response) but no study of the metabolic effects of this compound in the dog has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Using the latter approach we have sought to characterize the P-adrenoceptors that mediate inhibition of gastric secretion by studying the non-selective ,B-adrenoceptor agonist isoprenaline (Ekue, Shanks & Zaidi, 1971), the #2-selective agonist salbutamol (Cullum, Farmer, Jack & Levy, 1969) and their interactions with the /3l-and #2-adrenoceptor antagonist propranolol (Shanks, 1966), the fil-selective antagonist practolol (Dunlop & Shanks, 1968) and the f2-selective antagonist H35/25 (Levy, 1967). (+)-Propranolol, the inactive isomer of propranolol, was used as a control for effects unrelated to ,B-adrenoceptor blockade (Howe & Shanks, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Salbutamol (Fig. 7) is an effective drug used to treat conditions such as primary bronchial asthma [57] and cardiovascular disease [58], etc. Salbutamol was docked into the MD equilibrium structures of WT and mutated β2AR, respectively.…”
Section: Mm/gbsa Binding Free Energy Calculationmentioning
confidence: 99%